Optimization of Postoperative Analgesia in Patients with Nontoxic Goiter - M. I. Neimark; Ye. V Kotlyar; T. V. Ponimaskina; M. A. Neklyudova (Общая реаниматология, 2008)
Objective: to comparatively evaluate the analgesic activity and hemostatic effects of two nonsteroidal anti-inflammatory drugs (NSAID) that are most commonly used for postoperative analgesia — ketorolac and ketoprofen in patients operated on for diffuse nodular nontoxic goiter. Subjects and methods. At surgical treatment stages, the authors examined the degree of the pain syndrome by the visual analog scale and hemostatic parameters in 90 patients divided into three groups according to the postoperative analgesia mode (ketorol, ketonal, and promedol). Results. Postoperative analgesia in nontoxic goiter patients with ketorol and ketonal has been ascertained to be highly competitive with that with promedol and to give no rise to clinically significant complications inherent in NSAID. Ketorol provides a rapider, prolonged and effective postoperative analgesia than does ketonal. Ketorol affects the hemostatic system to a lesser extent than does ketonal. Conclusion. Ketorol analgesia may be considered to be the method of choice of postoperative analgesia in patients with nontoxic goiter. Key words: ketorol, ketonal, hemostasis, analgesia.